THE EFFECT OF ENCAPSULATION ON SOME PROPERITES OF LACTOBACILLUS PLANTRAUM - P. K. Faraj; T. A. AL-Nashi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The objective of the study was to enhance the survivability of Lactobacillus plantarum (ATCC 29521) and investigate their resistance to some extreme conditions following its microencapsulation with alginate, chitosan, and olibanum gum. The study’s findings showed that the use of olibanum gum in the first and second layers with alginate and chitosan protected the bacteria against various forms of pasteurization, as well as against extremely acidic conditions and high bile salt concentrations. After 28 days of storage at 4°C, the bacteria coated with the using of olibanum gum in the first and second layer demonstrated a great superiority in maintaining high numbers and better viability. The use of gum also contributed to increase the ability of the bacteria to withstand freezing storage at -18°C and re-thawing. The results also showed that olibanum gum was a superior cryoprotectant during freeze-drying process and storage for six months at 22 ℃. Also scanning electron microscope images showed that beads encapsulated with using of olibanum gum loaded a higher number of Lb. plantarum.